A 7,000-year-old multi-component arrow poison from Kruger Cave, South Africa - Justin Bradfield; Ian A. Dubery; Paul A. Steenkamp (iScience)
Summary: We present the results of a GC-MS and UHPLC-MS analysis of residue recovered from the marrow cavity of a 7,000-year-old bovid femur from Kruger Cave, South Africa. The femur was filled with an unknown substance into which were embedded three bone arrowheads, indicating that the femur served as a quiver. Our results reveal the presence of digitoxin and strophanthidin, both cardiac glycosides associated with hunting poisons. These two compounds, and others identified, do not occur in the same plants and thus indicate a multi-taxa recipe. This is the oldest unequivocal complex hunting poison recipe yet identified, notwithstanding the many chemically unsupported assertions of older examples. Furthermore, the identification of ricinoleic acid points to the possibility of ricin as a third toxin and lends credence to the 2012 interpretation of this compound’s presence on a 24,000-year-old wooden applicator at Border Cave, South Africa.